The endothelial activation and stress index is a potential prognostic indicator for patients with acute pancreatitis managed in the intensive care unit: a retrospective study - Wang, Jianjun; Chen, Xi; Qin, Chuan; Zeng, Xintao; Du, Xiaobo; Wang, Decai (Frontiers in Medicine, 2024)
Background The endothelial activation and stress index (EASIX) serves as a dependable and efficient surrogate marker for endothelial dysfunction, which plays an essential role in the pathophysiology of acute pancreatitis (AP). Hence, we investigated the prognostic value of EASIX in AP. Methods This was a retrospective study, using patient information obtained from the Medical Information Market for Intensive Care-IV (MIMIC-IV) database. EASIX was calculated using lactate dehydrogenase, serum creatinine, and platelet counts obtained during the first measurement within 24 h of admission. Patients were grouped into three cohorts based on log2-transformed EASIX. The main endpoint of the study was 28-day all-cause mortality (ACM) in AP patients, with the secondary endpoint being 90-day ACM. The relationship between EASIX and prognosis in patients with AP was evaluated using Cox proportional hazards models, Kaplan–Meier curves, restricted cubic spline (RCS) curves, and subgroup analyses. Receiver operating characteristic (ROC) curves were constructed to evaluate the predictive performance of EASIX compared to other indicators. Results The study cohort comprised 620 patients in total. Multivariate Cox proportional hazards analysis indicated that an increased log2 (EASIX) was linked to a higher risk of 28-day ACM in AP patients (HR, 1.32; 95% CI: 1.14–1.52; p < 0.001). The risk of 28-day ACM was higher in Tertiles 2 and 3 compared with Tertile 1 [(HR, 2.80; 95% CI: 1.21–6.45); (HR, 3.50; 95% CI: 1.42–8.66)]. Comparable findings were noted for 90-day ACM. Kaplan–Meier curves demonstrated that patients with elevated log2 (EASIX) had lower 28- and 90-day survival rates. The RCS curves suggested a non-linear relationship between log2 (EASIX) and 28- and 90-day ACM. ROC curves indicated that log2 (EASIX) was not inferior to sequential organ failure assessment and systemic inflammatory response syndrome scores in predicting the prognosis of patients with AP. Subgroup analyses demonstrated no interaction between log2 (EASIX) and any subgroup. Conclusion Elevated EASIX levels were significantly correlated with a heightened risk of 28- and 90-day ACM in AP patients.